Aboveground carbon sequestration in dry temperate forests varies with climate not fire regime. (1st June 2018) - Gordon, Christopher E.; Bendall, Eli R.; Stares, Mitchell G.; Collins, Luke; Bradstock, Ross A.
Abstract: The storage of carbon in plant tissues and debris has been proposed as a method to offset anthropogenic increases in atmospheric [CO2 ]. Temperate forests represent significant above‐ground carbon (AGC) "sinks" because their relatively fast growth and slow decay rates optimise carbon assimilation. Fire is a common disturbance event in temperate forests globally that should strongly influence AGC because: discrete fires consume above‐ground biomass releasing carbon to the atmosphere, and the long‐term application of different fire‐regimes select for specific plant communities that sequester carbon at different rates. We investigated the latter process by quantifying AGC storage at 104 sites in the Sydney Basin Bioregion, Australia, relative to differences in components of the fire regime: frequency, severity and interfire interval. To predict the potential impacts of future climate change on fire/AGC interactions, we stratified our field sites across gradients of mean annual temperature and precipitation and quantified within‐ and between‐factor interactions between the fire and climate variables. In agreement with previous studies, large trees were the primary AGC sink, accounting for 70% of carbon at sites. Generalised additive models showed that mean annual temperature was the strongest predictor of AGC storage, with a 54% near‐linear decrease predicted across the 6.1°C temperature range experienced at sites. Mean annual precipitation, fire frequency, fire severity and interfire interval were consistently poor predictors of total above‐ground storage, although there were some significant relationships with component stocks. Our results show resilience of AGC to frequent and severe wildfire and suggest temperature mediated decreases in forest carbon storage under future climate change predictions. Abstract : Temperate forests represent significant above‐ground carbon (AGC) "sinks" for climate change mitigation. However, climate and disturbance through wildfire may impact rates of carbon storage in these forests. We used a field survey to assess AGC storage in east Australian dry sclerophyll forests relative to mean annual temperature and precipitation and fire frequency and severity. Our results show resilience of AGC to variations in precipitation and wildfire regime. However, a 54% decrease in AGC was observed across the 6.1°C temperature gradient experienced at study sites. This suggests significant temperature mediated decreases in forest carbon storage given future climate change predictions.